(3GdJacjQ HTLGYI(B: (3GdJfhjQ HhUag YedjI eaJhMI(B/ s - Frick, Marie-Luisa (3aQjc, eGQj dhjRGs ((3GdbGgQI; s (3GdeMQhSI; s, 2023)
Title translation: Thinking with Courage: Enlightenment as an Open Process (3GdJfhjQ, acQI jfXQ EdjgG GdcKjQhf cMd TGed deTGcd GdYGde, NGUI aj GdYGde GdYQHj(B. (3dcf GdJfhjQ djS JLQHI KGHJI jecf JWHjbgG aj cd ReGf hecGf Ohf JacjQ(B. (3JbOe GdajdShaI GdCdeGfjI eGQj(B-(3dhjRG aQjc JhVjMkG ObjbkG deaghe GdJfhjQ, HOAkG ef adSaI cGfW hUhdkG Edi GdCacGQ GdeYGUQI(B. (3jJejR GdcJGH HJfGhd GdJfhjQ ceSDhdjI EfSGfjI jLH GdfXQ EdjgG HTcd fbOj hYdej dJJfGSH eY eJWdHGJ YUQfG GdMGdj(B. "Enlightenment" is a concept often seen as a comprehensive solution to the world$1 (Bs problems, especially in the Arab world. However, enlightenment is not a fixed experience that can be applied universally across all times and places without consideration. The German philosopher Marie-Luisa Frick offers a precise explanation of the concept of enlightenment, starting from Kant$1 (Bs philosophy and progressing through modern ideas. The book distinguishes itself by presenting enlightenment as a human responsibility that must be critically and scientifically viewed to align with the needs of our current era.s
Arabic
Keywords: B850-5739- Philosophy- By Period- Modern- By Region or Country; Enlightenment (3GdJfhjQs